Correlation Between Esophageal Varices and Lok Score as a Non-invasive Parameter in Liver Cirrhosis Patients - Iqbal Sungkar; Leonardo Basa Dairi; Gontar Alamsyah Siregar (The Indonesian Society for Digestive Endoscopy, 2016)
Background: Bleeding from gastro-esophageal varices is the most serious and life-threatening complication of cirrhosis. Endoscopic surveillance of esophageal varices in cirrhotic patients is expensive and uncomfortable for the patients. Therefore, there is a particular need for non-invasive predictors for esophageal varices. The aim of the present study was to evaluate association of esophageal varices and Lok Score as non-invasive parameter in liver cirrhosis patients.Method: This is a cross-sectional study of patients admitted at the Adam Malik hospital Medan between September to December 2014 with a diagnosis of cirrhosis based on clinical, biochemical, ultrasound, and gastroscopy. Lok Score was calculated for all patients, tabulated and analyzed.Results: Among 76 patients with esophageal varices, 55.3% was due to hepatitis B virus (HBV). The majority of patients were Child C with only 13,2% being Child Pugh class A. Majority of the population had F2 esophageal varices (42,1%), F1 (32,9%), and F3 (25%). There is significance difference between Lok Score and grading of esophageal varices, Lok score is higher in Large esophageal varices compared with small esophageal varises (0.92 ± 0.14 vs. 0.70 ± 0.29; p = 0.001). Lok Score cut-off value of 0,9141 was highly predictive in the diagnosis large esophageal varices with a sensitivity of 74.5%, specificity of 72%, positive predictive value of 84%, negative predictive value 58%, and accuracy was 73.7%.Conclusion: Lok Score was significantly associated with esophageal varices. Lok score is a good non-invasive predictor of large esophageal varices in cirrhotic patients.